Impact of a Peer-Family Connection Program on Social Belonging and Risk Behavior Reduction in Adolescents - Schneider, Lukas; Kovács, Eszter; Conti, Marco (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to evaluate the effectiveness of a peer-family connection program in enhancing social belonging and reducing risk behaviors among adolescents. Methods: A randomized controlled trial was conducted with 30 adolescents aged 13–16 from Hungary, who were randomly assigned to either an intervention group (n = 15) or a control group (n = 15). The intervention group participated in a seven-session, school-based Peer-Family Connection Program designed to improve interpersonal communication, emotional regulation, and relational bonding with peers and caregivers. Sessions were conducted weekly, lasting 45–60 minutes each. Social belonging and risk behavior were measured using validated standardized tools at pre-test, post-test, and five-month follow-up. Data were analyzed using repeated measures analysis of variance (ANOVA) and Bonferroni post-hoc tests in SPSS-27. Findings: Repeated measures ANOVA revealed a significant interaction effect between time and group for both social belonging (F(2, 56) = 17.08, p < .001, η² = .39) and risk behavior (F(2, 56) = 14.57, p < .001, η² = .34), indicating that the intervention group improved significantly over time compared to the control group. Bonferroni post-hoc analysis showed significant improvements in social belonging from pre-test to post-test (p < .001) and from pre-test to follow-up (p < .001), with no significant decline between post-test and follow-up. Similarly, risk behavior significantly decreased from pre-test to post-test (p < .001) and remained reduced at follow-up (p < .001), with no significant difference between post-test and follow-up. Conclusion: The Peer-Family Connection Program demonstrated sustained effectiveness in increasing adolescents’ social belonging and reducing their engagement in risk behaviors. These findings support the integration of relational interventions involving both peers and caregivers as a means to promote healthy adolescent development.